COMMUNICATION MODELS IN AGRICULTURAL EXTENSION FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - Umehai, Michael Chukwuemeka; Eromedoghene, Ezekiel Ovoh; Amafade, Ughwe Goodluck; Ebewore, Solomon Okeoghene (FUDMA JOURNAL OF SCIENCES, 2024)
This paper reviewed suitable communication models that bring about the changes in farmers’ behavior and farming practices for increase in the social economic status and livelihoods of farm families. The main focus of agricultural extension includes transferring knowledge from researchers, advising farmers on decision-making and educating farm families on how to make accurate decisions which will enable them clarify goals and stimulate desirable agricultural development. Disseminating innovations and technologies through extension education using various communication models involves agricultural and non-agricultural issues in the immediate environment and so the wellbeing of inhabitants in a particular area should be considered when using communication models. Advantages and disadvantages of these models are highlighted to show the relevance of communication models in agricultural extension and advisory services. The study highlights the implications of communication models in communicating agricultural and non-agricultural issues to farmers which is pertinent to agricultural productivity. It is recommended that competent extension agents properly trained in Information Communication Technologies (ICTs) extension approaches and the appropriate communication models educate farmers. Extension agents should also work with more contact farmers in various communities to have result oriented extension service delivery in Nigeria.
Keywords: Models; Information Communication Technologies; Agricultural Extension